The Effectiveness of Cadre Training using Cancer Educational Videos on Knowledge and Self-Efficacy - Kurniawan, Catur; Haryani, Haryani; Effendy, Christantie (Jurnal Keperawatan Soedirman, 2023)
Patients with cancer are at risk of death. There has been a lack of research on cancer-related training for health cadres. Meanwhile, they can potentially prevent cancer deaths because of their proximity to the community. This study aimed to determine the effectiveness of cancer educational videos on cadres’ knowledge and self-efficacy in Yogyakarta. This was quasi-experimental research with a nonequivalent control group design. The purposive sampling technique was used to obtain data from 61 health cadre respondents. The inclusion criteria: older than 19 years old, a woman, and uses WhatsApp. The Cancer Knowledge and General Self-Efficacy Scale Questionnaires measurement instruments were used. Data analysis was conducted using an independent sample t-test, repeated ANOVA, and paired comparison post hoc. There was a significant difference in respondents' knowledge in the control and intervention groups (p<0.05). The intervention group’s knowledge increased, and there was a moderate increase in knowledge in the control group. There was no significant change in cadres’ self-efficacy in the intervention group (p>0.05), but there was a significant increase (p<0.05) in the control group. Therefore, cadres’ training using cancer educational videos is effective for increasing cadres' knowledge only and not self-efficacy.